Physico-chemical properties of rain water harvested under different situations in lateritic - Abdu Ibrahim Hassen (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 2014)
Rain water harvesting is universally accepted as an important measure of water conservation throughout the world. The quality of irrigation water has become a more serious problem than quantity in different parts of the world. The characterization of quality of water is crucial for assessing the suitability for i rrigation. Hence a study was taken up on “Physico-chemical properties of rain water harvested under different situations in lateritic soil’’ in the main campus of Kerala Agricultural University, Vellanikkara during September, 2012 to August 2013. The objective of the study was to compare the physico-chemical properties of rain water from different water sources in lateritic soil. Water was collected from five sources viz, rainfall (RF), rain water harvesting pond (RWH) , Kotteppadom pond (KP), well water (W) and surface runoff (SR). The experiment for surface runoff study was laid out in an area with a gentle slope between 5 – 10 per cent . Four rain pits were dug in this area with dimensions of 0.5 m x 0.5 m x 0.5 m and lined by polyethene sheet. Water samples were taken from these water sources for one year at monthly intervals and they were analyzed for various physicochemical